Mining-related national systems of innovation in southern Africa: National trajectories and regional integration - Judith Fessehaie; Zavareh Rustomjee; Lauralyn Kaziboni (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper explores the linkages between the national systems of innovation of Botswana, South Africa, Zambia, and Zimbabwe and their respective mineral extraction and mineral processing value chains, including input industries. Our analysis reveals four individual national systems of innovation, with different outcomes in terms of engineering skills development, technical vocational education and training, research and development, innovation capabilities, and competitiveness of the domestic engineering consultancy services. These national systems of innovation are tentatively interconnected as an embryonic regional system of innovation, including institutional relationships, cross-border investment flows, flows of mining-related goods and services, and intra-Southern African Development Community flows of students, lecturers, technicians, and engineers. Notwithstanding important dynamics related to skills development and competence building happening across borders, more collaborative and synergistic initiatives between government, industry, and teaching and research institutions are required to shape a more balanced and coherent regional systems of innovation.
Keywords: L5; L6; O1; O25; O38; Q32; 330; national system of innovation; linkage development; human capital and industrialization; southern Africa; resource-based industrialization; Southern African Development Community